2015
DOI: 10.1038/onc.2015.396
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen identified let-7c/miR-99a/miR-125b regulating tumor progression and stem-like properties in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA), which is a poor prognosis malignancy that arises from the malignant transformation of cholangiocytes, is associated with chronic inflammation of the biliary epithelium. Thus far, the molecular mechanisms of the origin and neoplastic processes of CCA that are promoted by inflammation are still unclear and need to be fully elucidated. Here using small RNA sequencing to determine the microRNA (miRNA) expression profiles in CCA, we found that let-7c, miR-99a and miR-125b, which are three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
(69 reference statements)
4
55
0
Order By: Relevance
“…Generally, IL-6 was secreted by noncancer stem cells in low-attachment culture conditions and enriched Oct4 gene expression by activating the IL-6R/JAK/STAT3 signaling pathway in chronic inflammatory disease, such as cholangiocarcinoma [47, 48]. Our previously study also found treatment of CAA cells with IL-6 can active paracrine IL-6/STAT3 pathway in inflammation and CCA initiation [49]. IL-6 is a multifunctional inflammatory cytokine that plays a major role in the response of cholangiocytes to inflammation [40, 50]; and increased concentrations of IL-6 during inflammation in the biliary tract stimulates several pathways, including the JAK-STAT pathway, the p38 MAPK pathway, the ERK pathway, and the PI3-kinase pathway, and is involved in survival and growth of malignant cholangiocytes [40, 51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, IL-6 was secreted by noncancer stem cells in low-attachment culture conditions and enriched Oct4 gene expression by activating the IL-6R/JAK/STAT3 signaling pathway in chronic inflammatory disease, such as cholangiocarcinoma [47, 48]. Our previously study also found treatment of CAA cells with IL-6 can active paracrine IL-6/STAT3 pathway in inflammation and CCA initiation [49]. IL-6 is a multifunctional inflammatory cytokine that plays a major role in the response of cholangiocytes to inflammation [40, 50]; and increased concentrations of IL-6 during inflammation in the biliary tract stimulates several pathways, including the JAK-STAT pathway, the p38 MAPK pathway, the ERK pathway, and the PI3-kinase pathway, and is involved in survival and growth of malignant cholangiocytes [40, 51].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have realized that inflammation is one of important responses to the oxidative stress in many diseases, such as the gut [64], lung [65], pancreatitis [66], colorectal cancer [49], and cholangiocarcinoma [67]. Fernanda et al also reviewed a total of 1332 studies initially identified that TNF-a, IL-8, IL-6, IL-1b, and NF-κB were the main inflammatory mediators and oxidative stress markers [65], suggesting that the oxidative stress made a great contribution in inflammatory in the initiation or progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Both miR-99a and miR-491 may play different roles in various cancers as they regulated different target genes. The miR-99a has been reported to regulate resistance in breast cancer 18, leukemia 19, neck squamous cell carcinoma 20, germ cell tumor 21, pancreatic ductal adenocarcinoma 22, cholangiocarcinoma23, etc. The relation between miR-491 and liver cancer 24, colorectal cancer 25, ovarian carcinoma 26, pancreatic cancer 27, oral squamous cell carcinoma 28, non-small cell lung cancer 29, etc has also been verified.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125b has also been shown to promote stem cell-like properties in cholangiocarcinoma 62 and expand progenitor cell populations in acute megakaryoblastic leukemia 63 . Furthermore, miR-125b is significantly enriched in hair follicle stem cells and promotes initiation and malignant progression of skin tumors 45,64 .…”
Section: Discussionmentioning
confidence: 99%